Subclinical Scores in Self-Report Based Screening Tools for Attention Deficits Correlate With Cognitive Traits in Typical Evening-Type Adults Tested in the Morning - Korman, Maria; Levy, Ishay; Maaravi-Hesseg, Rinatia; Eshed-Mantel, Adi; Karni, Avi (Frontiers in Psychology, 2019)
Previous studies suggest that in adolescents and young adults, evening chronotype is a subclinical factor in physical, cognitive, and psychiatric fitness; poor sleep habits and larger misalignment with the social schedule constraints may exacerbate symptoms of inattention, impulsivity and the risks for detrimental behaviors. The influence of chronotype on neurocognitive performance during morning hours and scores in self-reports about attention deficit symptoms (ADS) and executive functioning, was explored in 42 healthy young university students (29 women), divided to evening type (ET) and combined morning/intermediate type (MT/IT) groups. Evening chronotypes scored significantly higher in the questionnaires of inattention Adult ADHD Self-Report Scale (ASRS-6) (MT/IT: 1.62 ± 1.59; ET: 2.71 ± 1.62, p < 0.05) and day-time sleepiness Epworth scale (MT/IT: 7.19 ± 5.17; ET: 11.48 ± 5.26, p < 0.01), reported lower subjective alertness (MT/IT: 63.02 ± 21.40; ET: 40.76 ± 17.43, p < 0.001), and had slower reaction times (MT/IT: 321.47 ± 76.81; ET: 358.94 ± 75.16, p < 0.05) during tests, compared to non-evening chronotypes. Nevertheless, ETs did not significantly differ in self-reports of executive functioning in the Behavioral Rating Inventory of Executive Functions-A (BRIEF-A) from non-ETs. The scores on standard self-report screening tools for ADS and executive functioning (ASRS-6, BRIEF-A-Metacognition) correlated with eveningness. We conclude that eveningness, subjective sleepiness and low arousal levels during morning can present as subclinical Attention Deficit and Hyperactivity Disorder (ADHD) symptoms in typical young adults with no evident sleep problems. Self-report based screening tools for ADS and executive functioning reflect chronotype-related traits in healthy young adults. Strong eveningness may bias the results of neurocognitive performance screening for ADHD when administered at morning hours.